Metode Presentasi Lintas Kelas Berkelompok: Alternatif Pembelajaran Menulis Karya Ilmiah Siswa Kelas XI MAN Demak - Muniâ€™ah Muniâ€™ah (Journal Prakarsa Paedagogia, 2022)
One of the purposes of â€œBest Practiceâ€ is to describe a method of cross-class presentation in groups as an alternative in learning to write scientific papers for the senior students of MAN Demak in the academic year of 2017-2018. Besides that, â€œBest Practiceâ€ is also used to find out the results or impact of the implementation of the cross-class presentation method in groups as an alternative in learning to write scientific papers for the senior students of MAN Demak in the academic year of 2017-2018. The results or impact of the implementation of the cross-class presentation method are, a) increasing student interest and motivation, b) Increasing student teamwork, c) Increasing student critical thinking and problem-solving skills, d) Improving student communication, e) Increasing student self-confidence, f) Student work in the form of scientific writings.